Relationship between Physical Activity and Quality of Life in Patients with Diabetes Mellitus - Metty Wuisang; Frendy Fernando Pitoy; Mutiara Wahyuni Manoppo; Silvia Dewi Mayasari Riu; Denny Maurits Ruku (Public Health of Indonesia, 2026)
Background: Engagement in Physical Activity (PA) is advised for those diagnosed with Diabetes Mellitus (DM); nevertheless, patients with DM frequently struggle to comply due to symptomatic manifestations, adversely affecting their quality of life (QoL). Objective: to examine the relationships between demographic characteristics, PA and QOL; Furthermore, this study was to identify predictors of QoL in patients with DM. Methods: This study uses a cross-sectional design. The measuring instruments used were demographic characteristics, the Five Times Sit-to-Stand Test (FTSST), the International Physical Activity Questionnaire (IPAQ), and the Quality of Life (EQ-5D-5L) Questionnaire for data collection.  Data was analyzed using the Pearson correlation coefficient, t-test, one-way ANOVA, and multiple hierarchical regression. Results: The mean age of 245 patients with DM was 59.91 ± 11.68 years, with 60.4% female, and the mean score QOL was 0.88 ± 0.10. QOL in patients with DM showed a significant relationship with sitting time, domains of PA (Occupational, Transportation, and Leisure time), and the total score IPAQ. Meanwhile, age, gender, marital status, living arrangement, education level, body mass index (BMI), duration of DM diagnosis, FTSST, and housework domain did not show significant correlations with QOL in patients with DM. Seven variables emerged as significant predictors of QOL in patients with DM: age, BMI, duration of DM diagnosis, sitting time, and domains of PA (occupational, transportation, and leisure time). Conclusion: Consistent PA is essential for enhancing the QOL of patients with DM. Moreover, sitting time, domains of PA (occupational, transportation, and leisure time), and total PA should be considered when delivering care to DM patients to enhance QOL.